Edutainment game for kids : learn about shapes aged 4 to 5 years old / Azura Abdullah - Abdullah, Azura (2005)
The system that has been developed is entitled 'Edutainment Game for Kids: Learn about Shapes' which focus on pre-school children aged between 4 to 5 years old. The content of this courseware is to teach children about basic shapes that exist in their surroundings. The system will be presented by using the combination of multimedia elements depending on a suitable topic. The target of this project is to deliver shapes learning with interesting and informative system to children. System approaches is to provide study courses and game by including multimedia elements such as text, soiind, images and animations into the system. Macromedia Flash MX 2004 is used as a platform for the development of the system. The navigational technique that is used for the system is sequential, exploratory and topical while the user interface design will be in the form of Graphical Direct Manipulation technique.